Perceptions of cognitive intercultural skills through exposure to summer learning camp activities (2016)
This paper will discuss the usefulness of a summer learning program as a means to report on the perceptions of cognitive intercultural skills, namely, cultural self-awareness, and culture/general/culture-specific knowledge. The samples of this research include pre-service teachers from the program of Bachelor of Education in English Language and two visitors from Germany and USA. They have an average age of 22 years old; three of them are women and seven are men. Data were collected through observation, stimulated recall interviews, and reflective journal methods. Results evidenced cultural differences among participants for establishing interpersonal relationships, and strengthening regarding culture-general and culture-specific knowledge by means of situations that promote spontaneous interactions such as mealtimes. Therefore, this research concluded that cultural exchanging among participants contributed to evidence campers’ perceptions in regard to the cognitive skills. Additionally, summer learning camps appear to be an effective strategy that could be implemented in other teaching programs in Colombia as means to promote intercultural competence since participants have the opportunity to interact directly with speakers from other cultures. That is to say, it is it essential to have foreigners in this type of programs.